A Low-power Liquid-fuelled Burner Using a Novel Atomization Concept. Issue 9 (2nd September 2019) - Goßmann, Ann-Kathrin; Müller, Thomas; Kühn, Johannes; Etzold, Mathias; Stelzner, Björn; Zarzalis, Nikolaos; Durst, Franz; Trimis, Dimostenis
ABSTRACT: The design of and experimental results for a low-power heating oil burner, operating between 1.25 and 5.1 kW with exhaust gas emissions within the normative regulations for domestic usage, are presented. In contrast to common domestic heating oil burners, the atomization and combustion sections are spatially separated to allow the implementation of a novel atomization concept for low-power liquid-fuelled burners proposed in a previous study. The main working principle for spray generation is the secondary atomization of a droplet chain impinging on a pin downstream. Through pulse-width modulation (PWM) of the droplet generator, modulation of the spray flowrate over a wide range with constant spray quality was achieved. Phase-Doppler anemometry measurements under non-reacting conditions were performed to obtain the droplet size distribution of the spray. Three model liquids were used to determine the influence of liquid properties on the droplet size distribution. The Sauter mean diameter (SMD) values obtained for all liquids and operation parameters studied are in the range of 10% of the primary droplet diameter, which is 30 µm for the setup in this study.